Interpretative Analysis of the Sonata for cello solo, op. 8. by Zoltán Kodály. A proprioceptive systematization - Romero Ottonello, José (2019)
The present research constitutes a foundation for technical problems involved in learning Sonata for cello solo,op. 8 by Zoltán Kodály. As part of a larger research project, this paper addresses specific points of the learning process. It proposes the study of two broad thematic sections. The first is autoethnography, addressing different problems observed through personal experience as a musical performer, and the second is the presentation of practical solutions in order to technical-interpretative dificults in the sonata performance, selected through the introspective search of the learning process.